A Study of Particle Trajectories In A Gas Turbine Intake - Tan, S. C. (Cranfield University, 1988)
An experimental and theoretical study of the particle trajectories in a gas turbine intake has been presented. computer model was written to simulate a particle behaviour flight in a theoretical flow which was assumed to inviscid, irrotational and incompressible. The model is also on other assumptions which imposes several limitations the accuracy of the predicted results. These limitations the objectives of the experimental investigation of particle trajectories which was carried out in a 30.0 section of an axisymmetric helicopter inertial separator. The separator section was fully instrumented with pressure tappings to determine the near-wall flow condition. The flowfield at the central (vertical) plane of separator was also measured with a two spot laser anemometer. The dust particles used in the tests were the spherical ballotini and irregular quartz particles with diameter ranging f-rom 15.0 to 150.0 microns. These particles seeded locally into the separator at three initial positions. The restitution ratios for the quartz particle based on experimental data and the ballotini particle's were based on a simple relation, which was derived by and error matching of predicted and experimental results. The particle trajectories, velocities and angles in separator were measured at several stations using the anemometer. The measured results were compared with predicted values from the model which has been modified accept both the experimentally measured and inviscid flowfield. The particle shape factor was also included to account for the higher drag on the non-spherical particle. Further modification was also made to include the restitution ratios of the ballotini particle. Good agreement found between measured and predicted particle trajecto- velocities and angles for both the spherical and non- spherical particle. The trajectories of the large particles (>100. Oum) are ballistic' in nature which are governed by the inertia forces. The trajectories of the smaller particles are influenced by the both aerodynamic and inertia forces.